Keefektifan Dosis Pac (Poly Aluminium Chloride) Terhadap Penurunan Kadar Tss (Total Suspended Solid) Limbah Industri Penyamakan Kulit Magetan - Artika Yuanita, Yuga; , Dwi Astuti, SKM., M.Kes; , Sri Darnoto. SKM. MPH (2015)
Liquid waste containing TSS can harm the environment and living beings. Based on preliminary survey TSS levels Tannery Industry Magetan is 68 mg / l, the results are above the quality standard of the East Java Governor Regulation No. 72 Year 2013 on Liquid Waste Quality Standard of 60 mg / l. One way that can be done to reduce rough TSS is coagulation with using PAC. This study aims to determine the effectiveness of the PAC dosage to reduce levels of TSS in wastewater. Variations PAC doses used were 0.5 g / l; 0.7 gr / l; and 1 g / l, percentage reduction in TSS levels at each dose that is 54.41%, 73.10% and 85.73%. The most effective dose of PAC used to lower levels of TSS in wastewater Magetan tanning industry with the highest percentage decrease of 1 g / l.